Case Report: Ultrasound-guided microwave ablation combined with postoperative radiotherapy and chemotherapy for advanced tongue cancer - Wei, Ting; Dai, Jiulong; Li, Tingting; Hu, Ziyue; Wang, Lu; Li, Juan; Zou, Jie; Feng, Jia; Lu, Man (Frontiers in Oncology, 2025)
BackgroundWhile surgery remains the standard treatment for tongue cancer, it is associated with a range of functional and aesthetic sequelae. Additionally, ultrasound-guided microwave ablation (MWA) represents a promising minimally invasive alternative for patients with poor performance status or those unwilling to undergo surgery.Case PresentationWe report a 50-year-old male patient diagnosed with advanced tongue squamous cell carcinoma and cervical lymph node metastases. Microwave ablation was performed using a power setting of 30 W. Contrast-enhanced ultrasound conducted immediately afterward revealed no enhancement in the ablation area. Following the ablation, the patient received adjuvant radiotherapy and chemotherapy. During the procedure, the patient experienced minimal pain and no significant complications. After more than two years of follow-up, no evidence of metastasis or recurrence was observed, and the patient retained normal speech and swallowing functions.ConclusionsUltrasound-guided MWA combined with radiotherapy and chemotherapy offers a safe, effective, and minimally invasive approach to the treatment of advanced tongue cancer.